2020
DOI: 10.3390/w12092572
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Mapping of the Rainfall–Landslides Disaster Chain Based on GeoDetector and Bayesian Network Models in Shuicheng County, China

Abstract: Landslides are among the most frequent natural hazards in the world. Rainfall is an important triggering factor for landslides and is responsible for topples, slides, and debris flows—three of the most important types of landslides. However, several previous relevant research studies covered general landslides and neglected the rainfall–topples–slides–debris flows disaster chain. Since landslide hazard mapping (LHM) is a critical tool for disaster prevention and mitigation, this study aimed to build a GeoDetec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 55 publications
0
21
1
Order By: Relevance
“…By incorporating this property of GeoDetector in hybrid GeoDIV model, among the fourteen conditioning factors initially collected, four of them (slope aspect, profile curvature, SPI, and mean annual rainfall) were identified as statistically insignificant and were not finally included in LS assessment. Similar factors were also eliminated as redundant in [14,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating this property of GeoDetector in hybrid GeoDIV model, among the fourteen conditioning factors initially collected, four of them (slope aspect, profile curvature, SPI, and mean annual rainfall) were identified as statistically insignificant and were not finally included in LS assessment. Similar factors were also eliminated as redundant in [14,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although GeoDetector has been tested in various studies of health, social and environmental sciences [20][21][22] over the last few years, its use in landslide-related research has been quite limited. Since it provides an effective way to identify and eliminate redundant variables, GeoDetector has been used in a few relevant studies [14,23,24] for factor selection purposes.…”
Section: Introductionmentioning
confidence: 99%
“…MCC was used to evaluate the cells in the ETL prediction maps relative to the reference landslide map. Several studies (Rong et al, 2020;Wang et al, 2020;Meena et al, 2021) have adopted MCC to evaluate landslide susceptibility maps. Rong et al (2020) obtained MCC 0.44 for a hazard map of rainfall-induced landslides in Shuicheng, China.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Several studies (Rong et al, 2020;Wang et al, 2020;Meena et al, 2021) have adopted MCC to evaluate landslide susceptibility maps. Rong et al (2020) obtained MCC 0.44 for a hazard map of rainfall-induced landslides in Shuicheng, China. Wang and Lin, 2010 compared four different landslide susceptibility mapping methods and found that MCC varied from 0.4 to 0.5.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…In this context, Kok et al [6] proposed a methodology to establish the most vulnerable regions in the Cameron Highlands, and Long and De Smedt [7] performed an analysis of the rainfall-induced landslide susceptibility in a district of Vietnam. Finally, Rong et al [8,9] used a Bayesian model for mapping the rainfall-induced landslides in China. These studies showed that the landslide mapping may be a useful tool for disaster prevention and hazard mitigation.…”
mentioning
confidence: 99%